LMS Moodle “Glossary” to organize an interactive event “Online round table” when teaching foreign languages at a university - Natalia V. Khudolei (RUDN Journal of Informatization in Education)
Problem statement . A round table is a reliable way to organize students’ communicative activities when teaching foreign languages. The innovative methods of working in Moodle educational environment allow the teacher to organize an online round table. The author’s methodology to use Glossary of LMS Moodle for development and implementation of an interactive online round table event to improve communication skills among university students while learning foreign languages is introduced. A definition of the online round table as an interactive type of work is proposed. Methodology . The peculiarity of LMS Moodle Glossary was tested and analyzed to create interactive communication tasks performed as the online round table. Results . Examples of the online round table tasks to improve and develop the communication skills of students are given and thoroughly explained. The techniques to make the online round table interactive tasks, and put them into operation by means of Glossary are shown in detail. Conclusion . Glossary of LMS Moodle to introduce the online round table interactive tasks for the development and improvement of university students’ communication skills when learning foreign languages has been proven to be very effective.